Pengaruh Medium Tumbuh Pada Pertumbuhan Biomassa Wolffia schleidenii Miq dan Kandungan Nutrisi Sebagai Bahan Pakan ternak - Adiguna Sasama Wahyu Utama; Anang Widigdyo (Universitas Islam Balitar, 2019)
This research aims to study the best medium for growing W. schleidenii and their nutrient contents. Different media were used to optimize the growth of W. schleidenii. Those used media were consisted of cow manure fertilizer with concentration of 5 g/l, 2.5 g/l, 1 g/l, goat manure fertilizer of 5 g/l, 2.5 g/l, 1 g/l, synthetic fertilizer of 100%, 75%, 50%, liquid ammonia wastes of 100 ppm, 50 ppm, 25 ppm and the water from poluted river. Spring water is used as a control medium. The parameters were biomass growth and the containt of nutrients. The results showed that the best growth of W. schleidenii occurred in the media of cow manure fertilizer of 2.5 gr/l. The plant could not grow well in the synthetic fertilizer and liquid ammonia wastes. It was found the nutrient contents of W. schleidenii were 74,26% of protein, 12,36% of carbohydrates, 1,54% of lipid, and 11,84% of crude fiber. Thus it is possible to consider this plant as resource of protein for feeding.